Germany and the use of force: The evolution of German security policy 1990-2003 - Longhurst, Kerry (Manchester University Press, 2004)
Mobilising the concept of strategic culture, this study develops a sophisticated and innovative framework to understand developments in German security policy between 1990 and 2003. Germany's contemporary security policies are characterised by a peculiar mix of continuity and change. From abstention in the first Gulf war, to early peacekeeping missions in Bosnia in the early 1990s and a full combat role in Kosovo in 1999, the pace of change in German security policy since the end of the Cold War has been breathtaking. The extent of this change has recently, however, been questioned, as seen most vividly in Berlin's response to '9/11' and its subsequent stalwart opposition to the US-led war on terrorism in Iraq in 2003. Beginning with a consideration of the notion of strategic culture, the study refines and adapts the concept to the case of Germany through a consideration of aspects of the rearmament of West Germany. The study then critically evaluates the transformation of the role of the Bundeswehr up to and including the war on terrorism, together with Germany's troubled efforts to enact defence reforms as well as the complex politics surrounding the policy of conscription. By focusing on both the 'domestics' of security policy decision making as well as the changing and often contradictory expectations of Germany's allies, this book provides a comprehensive analysis of the role played by Germany's particular strategic culture in shaping policy choices. The book concludes by pointing to the vibrancy of Germany's strategic culture and argues that it will continue to define Berlin's approach to the use of force. Crucially, this may mean that Germany's perspectives may depart substantially from those of its key partners and allies. This book is essential reading for all those interested in contemporary European security as well as German politics.